Spiritualitatea – ca dominantă a învăţământului (educaţiei) de nivel preşcolar/primar [Articol] - Zolotariov, Elena (USARB, 2014)
Article highlights scientifically substantiated solution for modernization of the educational process to facilitate the development of a free and independent personalities, able to think and act with moral responsibility. The study aimed at determining the conditions pedagogical awareness of the moral value of an act by the preschool and primary students. Research results reflect the author's attempt to build a model adjusted moral teaching process systems compatible with the rigors of space European value.
Keywords: spiritualitate; învăţământ preşcolar; învăţământ primar